Follow-up of endovascular aortic aneurysm repair: Preliminary validation of digital tomosynthesis and contrast enhanced ultrasound in detection of medium- to long-term complications - Mazzei, Maria Antonietta (World J Radiol, 2016)
AIM: To validate the feasibility of digital tomosynthesis of the abdomen (DTA) combined with contrast enhanced ultrasound (CEUS) in assessing complications after endovascular aortic aneurysm repair (EVAR) by using computed tomography angiography (CTA) as the gold standard. METHODS: For this prospective study we enrolled 163 patients (123 men; mean age, 65.7 years) referred for CTA for EVAR follow-up. CTA, DTA and CEUS were performed at 1 and 12 mo in all patients, with a maximum time interval of 2 d. RESULTS: Among 163 patients 33 presented complications at CTA. DTA and CTA correlated for the presence of complications in 32/33 (96.96%) patients and for the absence of complications in 127/130 (97.69%) patients; the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of DTA were 97%, 98%, 91%, 99%, and 98%, respectively. CEUS and CTA correlated for the presence of complications in 19/33 (57.57%) patients and for the absence of complications in 129/130 (99.23%) patients; the sensitivity, specificity, PPV, NPV and accuracy of CEUS were 58%, 99%, 95%, 90%, and 91%, respectively. Sensitivity, specificity and accuracy of combining DTA and CEUS together in detecting EVAR complications were 77%, 98% and 95%, respectively. CONCLUSION: Combining DTA and CEUS in EVAR follow-up has the potential to limit the use of CTA only in doubtful cases.